An investigation of the change in the severe material deprivation rate of Turkey - Atasü, Seniha İdil. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2017., 2017)
On September 2014, Turkish Statistical Institute has announced the results of the Income and Living Conditions Survey for 2013. According to the survey the severe material deprivation rate, which is defined as the percentage of population with an enforced lack of at least four out of nine material deprivation items in the economic strain and durables dimension, was calculated as 49.7% for 2013 whereas it was 59.2% for 2012. These numbers have been recalculated for the announcement made on 18 September 2015 and were updated to fall from 55% in 2012 to 42.8% in 2013 and to 29.4% in 2014. Following the announcement indicating a severe drop in the severe material deprivation rate, it was noted that 4 questions of the survey have been slightly changed. This study aims to find out if the drop in the severe material deprivation rate has its roots in the changed questionnaire as well as finding out if the change in the questionnaire has changed the material deprivation status of certain demographic groups.
Keywords: Poverty -- Turkey.; Economics -- Methodology.; Economics -- Sociological aspects.